Predictors of Self-Efficacy in Patients with Chronic Obstructive Pulmonary Disease - Scholastica Fina Aryu Puspasari (CV. Publikasi Indonesia, 2026)
Chronic obstructive pulmonary disease (COPD) is a growing global health concern with increasing morbidity and mortality. Self-efficacy plays a key role in COPD self-management, influencing patients’ ability to control symptoms, perform daily activities, manage emotions, and access health information. Identifying factors that affect self-efficacy is essential to improve patient outcomes and quality of life. This quantitative cross-sectional study involved 100 outpatient COPD patients at Respira Hospital Yogyakarta. Data were collected using the validated Indonesian version of the Chronic Self-Management Scale (CSMS) and analyzed through univariate and multiple linear regression methods. The mean self-efficacy score was 35.83 (SD = 7.609). Regression analysis showed that symptom management, activity management, emotional management, and information management collectively had a significant effect on self-efficacy (p = 0.001; R = 0.582; R² = 0.339). Partially, emotional management (p < 0.001) and information management (p = 0.026) were significant predictors, while symptom management (p = 0.092) and activity management (p = 0.266) were not. In conclusion, emotional and information management are key predictors of self-efficacy in COPD patients, with emotional management as the most dominant factor. Interventions should prioritize emotional regulation and improving health literacy to enhance self-efficacy and overall quality of life.